THE EFFECTIVENESS OF PERSONALIZED ADVERTISING ON CONSUMER ENGAGEMENT THROUGH EMOTIONAL ATTACHMENT ON SOCIAL MEDIA - Ringgo Syaputra; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to analyze the effectiveness of personalized advertising on consumer engagement through emotional attachment on social media. Personalized advertising is increasingly popular in this digital era because it can increase the relevance of messages delivered to consumers. In this context, emotional attachment plays an important role in building emotional attachment between consumers and brands, which in turn can increase consumer engagement to the advertisements displayed. The method used was a literature review, by collecting and analyzing various relevant literature, such as scientific journals, articles, books, and previous studies on personalized advertising, consumer engagement, and emotional attachment on social media. This study also discusses various findings from existing literature and identifies factors that influence the effectiveness of personalized advertising. The study results indicate that personalized advertising that is tailored to consumer preferences can strengthen emotional attachment and increase engagement levels. Therefore, companies need to use consumer data wisely to create a more personal and relevant advertising experience.